The article proposes mechanisms for reducing credit risks, taking into account insurance instruments, and develops proposals for improving financial literacy and financial inclusiveness of banking services. It also substantiates the relevance of improving: PROBLEMATIC ISSUES OF TAKING LOANS FROM COMMERCIAL BANKS - Xakimov, Odil (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article proposes mechanisms for reducing credit risks, taking into account insurance instruments, and develops proposals for improving financial literacy and financial inclusiveness of banking services. It also substantiates the relevance of improving the mechanisms for collecting innovative ideas and proposals from business entities, including entrepreneurs with experience in the field of banking services.